Preparation method of epoxy resin pre-dispersion liquid
Silicone rubber core-shell particles below 100nm were prepared by silicone microemulsion polymerization and liquid-liquid extraction technology, which solved the problems of uneven particle size and uneven dispersion in the prior art, and realized the preparation of high-performance epoxy resin predispersion, which was suitable for extreme environments.
Patent Information
- Application Number
- CN202510825407.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-08-12
AI Technical Summary
The prior art is difficult to prepare an epoxy resin predispersion with a silicone rubber core-shell structure with a particle size of less than 100 nm, resulting in poor toughening effect and uneven dispersion, making it difficult to meet the needs of high-performance materials.
Silicone rubber cores are prepared by silicone microemulsion polymerization, combined with liquid-liquid extraction technology, the particle size is controlled and dispersed in epoxy resin, and silicone rubber core-shell particles less than 100nm are prepared. Liquid-liquid extraction and redispersion technology is used to retain the original form to the greatest extent and remove impurities.
It has achieved high dispersion and high toughness of epoxy resin predispersion, with good low temperature resistance, weather resistance and high reactivity, and is suitable for extreme environmental applications.
Smart Images

Figure CN120464138A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of organosilicon material synthesis and polymer material synthesis, and in particular to a method for preparing an epoxy resin pre-dispersion liquid. Background Art
[0002] Epoxy resin is a thermosetting polymer, a type of high molecular weight polymer containing epoxy groups (-O-), typically produced by the polycondensation reaction of epichlorohydrin and polyols (such as bisphenol A). The epoxy group is the core functional group of epoxy resin, giving it high reactivity and excellent performance. It has excellent bonding properties and has strong adhesion to a variety of materials such as metals, ceramics, glass, and wood; it has outstanding mechanical strength, high hardness and good wear resistance after curing, and outstanding compressive and tensile properties; it is highly resistant to chemical corrosion and resistant to acid, alkali, solvent and oil corrosion; it has high insulation and arc resistance; it has low curing shrinkage, and the shrinkage rate during the curing process is low (about 1-2%), which can maintain dimensional stability. It is the most widely used and largest-volume matrix resin for the manufacture of polymer-based composite materials. However, epoxy resins exhibit high crosslink density, high brittleness, and poor impact resistance after curing. They are hard and brittle after curing and prone to cracking under severe impact. Furthermore, the basic structure of the cured product determines the limited high-temperature resistance of epoxy resins, which, to a certain extent, restricts their widespread application in high-tech fields. Therefore, research on toughening and high-temperature resistance modification of epoxy resins, as well as process performance optimization, has always been a focus of academic and industrial attention.
[0003] Toughening methods for epoxy resins mainly include liquid rubber toughening, thermoplastic resin toughening, nanoparticle toughening, core-shell toughening, interpenetrating network (IPN) toughening, and rigid particle toughening. Liquid rubber toughening (such as CTBN) is simple to operate and low-cost, but it significantly reduces strength, modulus, and heat resistance, and induces phase separation. Thermoplastic resins (such as PES) can improve toughness and have good heat resistance, but they significantly increase the viscosity of the system and lead to processing difficulties. Nanoparticle toughening (such as nano-SiO2) can simultaneously improve toughness, strength, and heat resistance, but it is difficult to disperse and has a high cost. IPN toughening improves overall performance by forming an interpenetrating network, but the process is complex. Rigid particle toughening (such as glass microspheres) mainly improves modulus and wear resistance, but has limited effect on toughness. In contrast, core-shell toughening achieves significant advantages through a soft core-hard shell structure (such as rubber core / PMMA shell): the soft core efficiently absorbs impact energy, and the hard shell has excellent compatibility with the epoxy resin matrix, which can not only greatly improve toughness and crack resistance, but also maintain strength, modulus and heat resistance. At the same time, it is evenly dispersed, has good processing performance, and improves interfacial bonding strength. Therefore, it has become the preferred solution in the fields of high-performance composite materials, electronic packaging and aerospace.
[0004] The particle size of a toughening agent significantly influences its toughening effect: Toughening agents smaller than 100nm have a high specific surface area and uniform dispersion, forming strong interfacial bonds that induce micro-cracks and shear bands, significantly improving toughness while maintaining strength, modulus, and heat resistance. They are suitable for high-precision electronic packaging and high-performance composite materials. Toughening agents between 100nm and 1μm enhance toughness through crack pinning and interfacial debonding, with a slightly less effective effect, but with less impact on mechanical properties, making them suitable for general structural materials. Toughening agents larger than 1μm, while capable of absorbing energy through cavitation, are prone to stress concentration and phase separation, significantly reducing strength, modulus, and heat resistance, resulting in poor toughening effects. Therefore, toughening agents smaller than 100nm have the best overall performance.
[0005] The rubber component of core-shell particles is typically composed of elastomers such as polybutadiene, polybutyl acrylate, and silicone rubber. Silicone rubber typically has a glass transition temperature (Tg) of -120°C to -80°C, much lower than that of polybutadiene rubber (-100°C to -80°C) and polybutyl acrylate rubber (-50°C to -20°C). This allows silicone rubber to maintain high elasticity even at ultra-low temperatures (such as -60°C), whereas the latter rapidly becomes brittle below its Tg. Furthermore, silicone rubber's molecular chain flexibility (low Si-O bond rotation barrier) imparts high-temperature stability (decomposition temperature > 250°C), whereas polybutadiene rubber softens easily above 100°C and polybutyl acrylate rubber significantly deforms at 120°C. Therefore, silicone rubber's wide temperature range (covering Tg to decomposition temperature) makes it a preferred choice for use in extreme environments (such as aerospace seals and polar equipment). The other two rubbers are limited by their limited Tg and temperature resistance.
[0006] Among the core-shell structure pre-dispersions currently available on the market, the average particle size of the polybutadiene rubber (PB) core-shell system can be controlled at about 100nm, while the particle size of the silicone rubber core-shell system generally exceeds 200nm. Since the difference in particle size directly affects the toughening efficiency (small particle size is more likely to induce microcracks and evenly disperse stress), the toughening effect of polybutadiene core-shell in matrices such as epoxy resin is significantly better than that of the silicone rubber system. Therefore, the development of silicone rubber core-shell pre-dispersions with a particle size below 100nm has become a key breakthrough in improving the toughness of high-performance materials. By reducing the particle size of silicone rubber core-shell to less than 100nm, it is expected to break through its toughening bottleneck while retaining the inherent high temperature resistance, weather resistance and biocompatibility advantages of silicone rubber, providing a better solution for extreme environment applications such as aerospace and electronic packaging.
[0007] Microemulsion polymerization is a technique that uses surfactants to construct thermodynamically stable nanoscale (10-100 nm) micelles as a "reactor" to directly synthesize monodisperse polymer particles in a system consisting of an oil phase, an aqueous phase, and additives. By precisely controlling the micelle structure, core-shell or functionalized nanomaterials (such as silicone rubber / epoxy resin composite particles) can be prepared, offering the advantages of uniform particle size, low temperature, and high efficiency.
[0008] Chinese patent CN113831455A reports a core-shell particle for epoxy resin toughening and its preparation method. Non-patent literature (LiY, Peng S, Miao JT, et al. Chemical Engineering Journal, 2020, 394: 124873) reports a core-shell particle containing an epoxy group, the core of which is styrene-butadiene rubber and the outside is an acrylate copolymer. However, these methods have the following characteristics: (1) The acquisition of core-shell particles requires continuous post-processing operations such as demulsification solid-liquid separation, centrifugal drying or freeze drying, and the process redundancy is high. (2) Subsequent dispersion still requires high shear or three-roller processing. Even so, the dispersion of core-shell particles in epoxy resin still has uneven phase distribution and local agglomeration. Therefore, how to simply prepare high-performance nano-silicone rubber core-shell particles (especially less than 100nm) epoxy resin pre-dispersion is a great technical challenge. Summary of the Invention
[0009] In order to solve the problems of the prior art, the purpose of the present invention is to provide a method for preparing an epoxy resin pre-dispersion liquid. The preparation method is to obtain a silicone rubber core less than 100nm by organosilicon microemulsion polymerization, and then adjust the final rubber core particle size by adjusting the amount of subsequent organosilicon monomers, and then use this as a seed for structural design, and ensure that its original form is dispersed in the epoxy resin to the greatest extent through liquid-liquid extraction, and wash out most of the impurities. The preparation method is simple and effective and can be produced on a large scale. The core-shell structure of organosilicon, the particle size less than 100nm, and the liquid-liquid extraction and redispersion technology provide good low temperature resistance, weather resistance, high toughness and good dispersion stability.
[0010] In order to achieve the above object, the technical solution adopted in the present invention is:
[0011] A method for preparing an epoxy resin pre-dispersion liquid comprises the following steps:
[0012] (1) 500 parts by weight of an organosilicon monomer, 1-100 parts by weight of a silane coupling agent, and 1-100 parts by weight of a double-bond silane coupling agent are uniformly mixed to obtain an organosilicon monomer mixed solution; 1-50 parts by weight of an acid or base catalyst and 1-500 parts by weight of deionized water are uniformly mixed to obtain an acid or base catalyst solution;
[0013] (2) by weight, 1-50 parts of emulsifier, 0-50 parts of co-emulsifier, 0-400 parts of deionized water and 0%-100% of acid or base catalyst liquid prepared in step (1) are mechanically stirred and heated to 20°C-90°C, 1%-100% of organosilicon monomer mixed solution prepared in step (1) and 0%-100% of acid or base catalyst liquid are added dropwise within 1min-360min, the temperature is raised to 50°C-95°C, and the reaction is carried out for 5min-240min, the remaining organosilicon monomer mixed solution and acid or base catalyst liquid are added dropwise within 0.5h-6h, the reaction is carried out at a constant temperature for 1h-6h, the temperature is lowered to 10-40°C, the pH is adjusted to 4-10 with alkaline aqueous solution or acidic aqueous solution, and the silicone rubber core emulsion is filtered;
[0014] (3) emulsifying 1-50 parts by weight of a double bond-containing monomer, 0.01-5 parts by weight of an emulsifier, and 3-30 parts by weight of deionized water using a high shear emulsifier for 1 minute to 10 minutes to obtain a double bond-containing pre-emulsion;
[0015] 1-25 parts of functional monomer, 1-50 parts of double bond-containing monomer, 0.01-5 parts of emulsifier, and 1-50 parts of deionized water are emulsified in a high shear emulsifier for 1 min-10 min to obtain a functional monomer emulsion;
[0016] 0-1 parts of buffer and 0-50 parts of deionized water are stirred and dissolved to obtain a buffer solution;
[0017] 0.01-5 parts of catalyst and 1-500 parts of deionized water are stirred and dissolved to obtain a catalyst solution;
[0018] (4) By weight, 100 parts of silicone rubber core emulsion, 0.01-5 parts of emulsifier, 1-50 parts of deionized water and the buffer solution prepared in step (3) are stirred and heated to 40-90° C., 1%-60% of the double bond-containing pre-emulsion prepared in step (3) and 1%-100% of the catalyst solution are added dropwise within 1 min-30 min, the temperature is raised to 50-90° C., the reaction is carried out for 1 min-120 min, the remaining double bond-containing pre-emulsion and 1%-99% of the catalyst solution are added dropwise within 0.5 h-4 h, the temperature is raised to 60-95° C., and the reaction is carried out for 0.5 h-6 h;
[0019] (5) cooling to 30-90° C., adding the functional monomer emulsion prepared in step (3) and the remaining catalyst solution dropwise within 1 min-120 min, heating to 50-95° C. and reacting for 0.5 h-6 h to prepare a silicone rubber core-shell emulsion;
[0020] (6) Add 20-400 parts of solvent by weight to the reaction kettle, start stirring at room temperature, and add 100 parts of silicone rubber core-shell emulsion dropwise within 1 minute to 60 minutes for extraction. Continue stirring for 1 minute to 30 minutes after the addition, and then stand for stratification for 0.5 hours to 24 hours, remove the lower aqueous layer, and obtain the upper silicone rubber core-shell particle solvent dispersion;
[0021] (7) By weight, 10-1000 parts of the prepared silicone rubber core-shell particle solvent dispersion and 100 parts of epoxy resin are added to a reaction kettle and stirred, and then the temperature is raised to 60-120° C. and the solvent is removed by vacuum distillation for 0.5 h to 24 h to prepare an epoxy resin pre-dispersion.
[0022] Preferably, the organosilicon monomer in step (1) is one or a combination of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, octaphenylcyclotetrasiloxane, methylphenylcyclosiloxane, tetravinyltetramethylcyclotetrasiloxane, low molecular weight hydroxy silicone oil, etc.
[0023] Preferably, the silane coupling agent described in step (1) is methyltrimethoxysilane, methyltriethoxysilane, octyltriethoxysilane, phenyltrimethoxysilane, phenyltrimethoxysilane, tetraethyl silicate, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-mercaptopropyl-trimethoxysilane, etc., or a combination thereof.
[0024] Preferably, the double bond-containing silane coupling agent in step (1) is one or a combination of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinyl-tris(2-methoxyethoxy)silane, etc.
[0025] Preferably, the acid catalyst in step (1) is one or a combination of benzenesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, formic acid, perchloric acid, etc. The base catalyst is one or a combination of sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, ammonia water, sodium oxide, potassium oxide, sodium methoxide, sodium ethoxide, potassium ethoxide, sodium tert-butoxide, tetramethylammonium hydroxide, etc.
[0026] Preferably, the emulsifier in steps (2) to (4) is one or a combination of sodium lauryl sulfate, sodium cetyl sulfate, sodium docusate, sodium dodecyl sulfonate, sodium dodecylbenzenesulfonate, dodecylbenzenesulfonic acid, sodium didodecylphenyl ether disulfonate, fatty acid polyoxyethylene ester phosphate, sodium rosinate, sodium cyclohexane, sodium ricinoleate, isomeric tridecyl alcohol ether, polyoxyethylene octylphenol ether-10, sorbitan monolaurate, sorbitan monopalmitate, dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, dodecyldimethylbenzyl ammonium chloride, etc.
[0027] Preferably, the co-emulsifier in step (2) is one or a combination of n-butanol, n-pentanol, ethylene glycol, ethanol, propylene glycol, isopropyl alcohol, polyvinyl alcohol, polyethylene glycol, acetone, butanone, ethyl acetate, methyl acetate, glycerol, polyglycerol ester, sodium chloride, sodium sulfate, sodium bicarbonate, etc.
[0028] Preferably, the alkaline aqueous solution in step (2) is one or a combination of ammonia water, sodium hydroxide aqueous solution, sodium bicarbonate aqueous solution, sodium formate aqueous solution, sodium acetate aqueous solution, ammonium acetate aqueous solution, disodium hydrogen phosphate aqueous solution, dipotassium hydrogen phosphate aqueous solution, sodium pyrophosphate aqueous solution, sodium phosphate aqueous solution, etc. The acidic aqueous solution is one or a combination of benzenesulfonic acid aqueous solution, p-toluenesulfonic acid aqueous solution, dodecylbenzenesulfonic acid aqueous solution, hydrochloric acid aqueous solution, sulfuric acid aqueous solution, phosphoric acid aqueous solution, acetic acid aqueous solution, formic acid aqueous solution, perchloric acid aqueous solution, etc.
[0029] Preferably, the double bond-containing monomer in step (3) is one or a combination of styrene, acrylonitrile, methyl methacrylate, butyl acrylate, isooctyl acrylate, acrylic acid, lauryl methacrylate, acrylamide, glycidyl methacrylate, allyl glycidyl ether, allylamine, 4-vinylaniline, 4-penten-1-amine, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 1-penten-3-ol, acrylic acid, methacrylic acid, methylenesuccinic acid, maleic acid, crotonic acid, allyl methacrylate, divinylbenzene, dicyclopentadiene acrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, trimethylolpropane trimethacrylate, triallyl isocyanurate, ethoxypentaerythritol tetraacrylate, etc.
[0030] Preferably, the functional monomer described in step (3) is one or a combination of epoxy-containing monomers (including but not limited to) glycidyl methacrylate and allyl glycidyl ether; amino-containing monomers (including but not limited to) allylamine, 4-vinylaniline, and 4-pentene-1-amine; hydroxyl-containing monomers (including but not limited to) hydroxyethyl methacrylate, hydroxypropyl methacrylate, and 1-pentene-3-ol; and carboxyl-containing monomers (including but not limited to) acrylic acid, methacrylic acid, methylenesuccinic acid, maleic acid, and crotonic acid.
[0031] Preferably, the buffering agent in step (3) is one or a combination of sodium bicarbonate, sodium formate, sodium acetate, ammonium acetate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, sodium pyrophosphate, sodium phosphate, etc.
[0032] Preferably, the catalyst in step (3) is one or a combination of dicumyl peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, benzoyl peroxide, azobisisobutylonitrile initiator, azobisisoheptylonitrile, etc.
[0033] Preferably, the solvent in step (6) is one or a combination of methyl formate, ethyl acetate, vinyl acetate, cyclohexanone, acetone, butanone, methyl isobutyl ketone, ethanol, isopropanol, triethylene glycol, propylene glycol, diethanolamine, triethanolamine, cyclohexane, n-hexane, n-heptane, xylene, toluene, dimethylformamide, acetonitrile, N-methylpyrrolidone, ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol butyl ether, styrene, perchloroethylene, trichloroethylene, ethylene glycol ether, chloroform, dichloroethane, dichloromethane, etc.
[0034] Preferably, the epoxy resin described in step (7) is one or a combination of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, epoxidized olefin compound, heterocyclic and mixed epoxy resin, etc.
[0035] This invention utilizes the above technical solution to prepare silicone rubber microemulsions / miniemulsions (with an average particle size of less than 100 nm) from organosilicon monomers via emulsion polymerization. This is then used as a seed to graft an intermediate layer of polyacrylate and an outermost layer of polyacrylate with reactive groups to produce core-shell particles. These core-shell particles are dispersed in epoxy resin via liquid-liquid extraction, resulting in high dispersibility. The core is silicone rubber, with a low glass transition temperature, which provides high and low-temperature performance. The intermediate and outermost layers provide access points to the resin, imparting high reactivity, good compatibility, and dispersibility.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The present invention can prepare silicone rubber core-shell epoxy resin pre-dispersion liquid with a particle size below 100 nm, which can make up for the market shortage and provide excellent performance.
[0038] 2. The present invention uses liquid-liquid extraction and redispersion technology to retain the original form and remove impurities to the greatest extent, and has a simple process, low cost, high production efficiency, and can be produced on a large scale.
[0039] 3. The outermost layer of the product of the present invention has reactive functional groups, which can be incorporated into the molecules during epoxy resin curing, thereby maximizing its toughness and making it highly reactive.
[0040] 4. While the present invention makes up for the shortcomings of epoxy resin, the refractive index of the silicone rubber core and the epoxy resin is quite different, which can make the resin whiter, play a whitening role, reduce the use of other auxiliary raw materials, and has good UV light transmittance, and can be used for 3D printing. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1It is the particle size distribution diagram of the silicone rubber core emulsion (a), silicone rubber core-shell emulsion (b) and epoxy resin pre-dispersion liquid (c) prepared in Example 1 of the present invention.
[0042] Figure 2 It is the SEM diagram of the cross section after curing with the formulation of the epoxy resin pre-dispersion liquid prepared in Example 1 of the present invention.
[0043] Figure 3 It is the model printed by a 355 nm 3D printer after adding the formulation of the epoxy resin pre-dispersion liquid prepared in Example 1 of the present invention. Specific embodiments
[0044] In order to further explain the technical solution of the present invention, the present invention will be elaborated in detail through specific examples below.
[0045] The present invention is measured and evaluated according to the following methods.
[0046] 1. Solids content
[0047] Weigh 2 g of the emulsion and place it in an oven at 120 °C for 1 h, or weigh 2 g of the dispersion liquid and place it in an oven at 100 °C for 0.5 h. Solids content = weight after drying g / 2 g × 100%.
[0048] 2. Average particle size and polydispersity index PDI of rubber particles and core-shell particles
[0049] The average particle size and polydispersity index PDI are measured by Zetasizer Nano ZS90. The emulsion is diluted with deionized water as the test sample, and the dispersion liquid is diluted with acetone as the test sample. The refractive index of the corresponding dispersion medium (water / acetone) and the refractive index of each rubber particle or core-shell particle are input for testing. PDI = 0 indicates that the particle system is completely monodisperse, that is, the sizes of all particles are exactly the same; PDI < 0.1 indicates that the system has a very narrow particle size distribution, and the particle sizes and distributions are very uniform; 0.1 < PDI < 0.5 indicates that the particle size distribution is relatively uniform and the particle sizes are relatively consistent; PDI > 0.5 indicates that the particle size distribution in the system is relatively wide, there is a large degree of polydispersity, and the particle uniformity is poor; PDI > 1 usually means that the particle size distribution is very wide and the polydispersity is significant.
[0050] 3. Viscosity of epoxy resin pre-dispersion liquid
[0051] The viscosity of the epoxy resin pre-dispersion liquid is tested by a Brookfield RVDV2T rotational viscometer. The No. 27 rotor is selected to test the viscosity at 50 °C.
[0052] 4. Impact resistance adhesion (wedge impact method)
[0053] Symmetrical wedge test pieces were prepared according to the wedge method specified in GB / T 36877-2018, Adhesives - Determination of Impact Peel Strength. Tests were conducted at 25°C, -30°C, and -40°C with an impact velocity of 2 m / s and an impact energy of 50 J.
[0054] Example 1
[0055] (1) 100.0 g of octamethylcyclotetrasiloxane, 3.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 1.0 g of sulfuric acid and 90.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0056] (2) To a four-necked flask equipped with a constant temperature water bath jacket and a reflux condenser and a mechanical stirrer, 2 g of sodium dodecylbenzenesulfonate, 0.2 g of n-butanol, and 130.0 g of deionized water were added, and the mixture was stirred and heated to 50° C., and 50% of the silicone monomer mixture and 90% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The mixture was heated to 75° C. and reacted for 60 minutes. The remaining silicone monomer mixture and the acid catalyst were added dropwise within 1 hour, and the mixture was reacted at a constant temperature for 2 hours. The pH was adjusted to 8 with sodium hydroxide aqueous solution, and the silicone rubber core emulsion was obtained by filtration. The solid content was 41.9%, the average particle size was 89.66 nm, and the PDI was 0.051.
[0057] (3) 0.25 g of sodium dodecylbenzene sulfonate, 12.5 g of deionized water, 20 g of styrene, and 5.0 g of divinylbenzene were added to a beaker in sequence, and emulsified for 2 min using a high shear emulsifier to obtain a styrene pre-emulsion;
[0058] 0.2 g of sodium dodecylbenzenesulfonate, 1.0 g of deionized water, 1.0 g of allyl glycidyl ether, 0.8 g of styrene, and 0.2 g of divinylbenzene were added to a beaker in sequence, and emulsified for 2 min using a high shear emulsifier to obtain an allyl glycidyl ether emulsion;
[0059] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0060] 0.27 g of potassium persulfate and 45.0 g of deionized water were added to a beaker, and the mixture was stirred and mixed to obtain a catalytic solution.
[0061] (4) To a four-necked flask equipped with a reflux condenser and a mechanical stirrer, 0.5 g of sodium dodecylbenzenesulfonate, 6.7 g of deionized water, 233.3 g of the silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C. Within 5 minutes, 50% of the styrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise, and the mixture was heated to 85° C. for 1 hour, and then the remaining styrene pre-emulsion and 30% of the catalyst solution were added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 2 hours.
[0062] (5) Cooling to 70° C., adding the allyl glycidyl ether emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 min, heating to 85° C. and reacting for 1 h to prepare a silicone rubber core-shell emulsion with a solid content of 38%, an average particle size of 94.68 nm, and a PDI of 0.082.
[0063] (6) At room temperature, 200 g of ethyl acetate and 80 g of butanone were added to the reactor, stirring was started, and 300.0 g of the silicone rubber core-shell emulsion was added dropwise within 2 min. Stirring was continued for 5 min after the addition was completed. Finally, the mixture was allowed to stand for 2 h. The upper and lower layers were completely separated. The lower layer was removed to obtain a transparent blue silicone rubber core-shell dispersion with a solid content of 29.5%.
[0064] (7) 84.8 g of silicone rubber core-shell dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C and distilled under reduced pressure for 1 h without solvent removal to obtain a silicone rubber core-shell particle epoxy resin pre-dispersion (Z-1). The core-shell content was 25%, the average particle size was 8 nm, the PDI was 0.078, and the viscosity was 2986 CP at 50°C.
[0065] See attached Figure 1 , which are particle size distribution diagrams of the silicone rubber core emulsion, silicone rubber core-shell emulsion, and silicone rubber core-shell particle epoxy resin pre-dispersion liquid in Example 1 of the present invention. Figures (a), (b), and (c) correspond to the particle size distribution diagrams of the silicone rubber core emulsion, silicone rubber core-shell emulsion, and silicone rubber core-shell particle epoxy resin pre-dispersion liquid, respectively. Their average particle sizes are all less than 100 nm, and their PDIs are all less than 0.1, indicating that the system has a very narrow particle size distribution and the particle size and distribution are very uniform.
[0066] See attached Figure 2 This is an SEM image of a cross-section of silicone rubber core-shell particles after curing after adding epoxy resin pre-dispersion to the formula in Example 1 of the present invention. The core-shell particles are uniformly distributed and sized, averaging around 100 nm, which is consistent with the particle size test results.
[0067] See attached Figure 3This model is a 355nm 3D printer printed with the epoxy resin pre-dispersion of silicone rubber core-shell particles prepared in Example 1 of the present invention. The successful printing of the model demonstrates its suitability for 3D printing. The model's white color indicates a whitening effect, reducing the use of other auxiliary raw materials.
[0068] Example 2
[0069] (1) 100.0 g of octamethylcyclotetrasiloxane, 3.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 1.2 g of sulfuric acid and 90.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0070] (2) To a four-necked flask equipped with a constant temperature water bath jacket and a reflux condenser and a mechanical stirrer, 2.5 g of sodium dodecylbenzenesulfonate, 0.25 g of n-butanol, and 130.0 g of deionized water were added, and the mixture was stirred and heated to 50° C., and 60% of the organic silicon monomer mixture and 90% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The mixture was heated to 75° C. and reacted for 60 minutes. The remaining organic silicon monomer mixture and the acid catalyst were added dropwise within 1 hour, and the mixture was reacted at a constant temperature for 3 hours. The pH was adjusted to 8 with sodium hydroxide aqueous solution, and the silicone rubber core emulsion was obtained by filtration. The solid content was 42%, the average particle size was 80.73 nm, and the PDI was 0.044.
[0071] (3) 0.25 g of sodium dodecylbenzene sulfonate, 12.5 g of deionized water, 20.0 g of styrene, and 5.0 g of divinylbenzene were added to a beaker in sequence and emulsified using a high shear emulsifier for 5 min to obtain a styrene pre-emulsion;
[0072] 0.2 g of sodium dodecylbenzenesulfonate, 1.0 g of deionized water, 1.0 g of allyl glycidyl ether, 0.8 g of styrene, and 0.2 g of divinylbenzene were added to a beaker in sequence, and emulsified for 2 min using a high shear emulsifier to obtain an allyl glycidyl ether emulsion;
[0073] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0074] 0.41 g of potassium persulfate and 68.0 g of deionized water were added to a beaker, and the mixture was stirred and mixed to obtain a catalytic solution.
[0075] (4) To a four-necked flask equipped with a reflux condenser and a mechanical stirrer, 0.5 g of sodium dodecylbenzenesulfonate, 7.3 g of deionized water, 232.7 g of silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C. Within 5 minutes, 50% of the styrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise, and the mixture was heated to 85° C. and reacted for 0.5 hours. The remaining styrene pre-emulsion and 30% of the catalyst solution were then added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 2.5 hours.
[0076] (5) Cooling to 70° C., adding the allyl glycidyl ether emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 min, heating to 85° C. and reacting for 1 h to prepare a silicone rubber core-shell emulsion with a solid content of 38.1%, an average particle size of 84.68 nm, and a PDI of 0.079.
[0077] (6) At room temperature, 300.0 g of ethyl acetate was added to the reactor, stirring was started, and 300.0 g of silicone rubber core-shell emulsion was added dropwise within 5 min. Stirring was continued for 5 min after the addition was completed. Finally, the mixture was allowed to stand for 2 h. The upper and lower layers were completely separated. The lower layer was removed to obtain the upper transparent white silicone rubber core-shell dispersion with a solid content of 29.7%.
[0078] (7) 84.28 g of silicone rubber core-shell dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C with stirring and then distilled under reduced pressure for 2 h without solvent removal to obtain a silicone rubber core-shell epoxy resin pre-dispersion (Z-2) with a core-shell content of 25%, an average particle size of 88.00 nm, a PDI of 0.034, and a viscosity of 3320 CP at 50°C.
[0079] Example 3
[0080] (1) 100.0 g of octamethylcyclotetrasiloxane, 3.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 1.5 g of sulfuric acid and 80.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0081] (2) To a four-necked flask equipped with a constant temperature water bath jacket and a reflux condenser and a mechanical stirrer, 2.0 g of sodium dodecylbenzenesulfonate, 0.5 g of sodium dodecyl sulfate, 0.25 g of n-butanol, and 140.0 g of deionized water were added, and the mixture was stirred and heated to 50° C., and 60% of the organic silicon monomer mixture and 100% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The mixture was heated to 75° C. and reacted for 60 minutes. The remaining organic silicon monomer mixture was added dropwise within 2 hours, and the mixture was kept at a constant temperature for 4 hours. The pH was adjusted to 8 with an aqueous sodium hydroxide solution, and the mixture was filtered to obtain a silicone rubber core emulsion with a solid content of 42.5%, an average particle size of 73.83 nm, and a PDI of 0.015.
[0082] (3) 0.25 g of sodium dodecylbenzene sulfonate, 12.5 g of deionized water, 20.0 g of styrene, and 5.0 g of divinylbenzene were added to a beaker in sequence and emulsified using a high shear emulsifier for 3 min to obtain a styrene pre-emulsion;
[0083] 0.2 g of sodium dodecylbenzenesulfonate, 1.0 g of deionized water, 1.0 g of allyl glycidyl ether, 0.8 g of styrene, and 0.2 g of divinylbenzene were added to a beaker in sequence, and emulsified using a high shear emulsifier for 3 min to obtain an allyl glycidyl ether emulsion;
[0084] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0085] Add 0.27 g of potassium persulfate and 45 g of deionized water into a beaker, and stir to mix evenly to obtain a catalytic solution.
[0086] (4) To a four-necked flask equipped with a reflux condenser and a mechanical stirrer, 0.5 g of sodium dodecylbenzenesulfonate, 10.0 g of deionized water, 230.0 g of the silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C. Within 20 minutes, 50% of the styrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise, and the mixture was heated to 85° C. and reacted for 2 hours. The remaining styrene pre-emulsion and 30% of the catalyst solution were then added dropwise within 120 minutes, and the mixture was reacted at a constant temperature for 6 hours.
[0087] (5) Cooling to 70° C., adding the allyl glycidyl ether emulsion prepared in step (3) and the remaining catalyst solution dropwise within 40 min, heating to 85° C. and reacting for 1.5 h to prepare a silicone rubber core-shell emulsion with a solid content of 38.1%, an average particle size of 75.11 nm, and a PDI of 0.013.
[0088] (6) At room temperature, 600.0 g of acetone was added to the reactor, stirring was started, and 300.0 g of the silicone rubber core-shell emulsion was added dropwise within 2 min. Stirring was continued for 10 min after the addition was completed. Finally, the mixture was allowed to stand for 5 h. The upper and lower layers were completely separated. The lower layer was removed to obtain a transparent white silicone rubber core-shell dispersion with a solid content of 30.7%.
[0089] (7) 81.4 g of silicone rubber core-shell dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C and distilled under reduced pressure for 5 h without solvent removal to obtain a silicone rubber core-shell particle epoxy resin pre-dispersion (Z-3). The core-shell content was 25%, the average particle size was 78.39 nm, the PDI was 0.025, and the viscosity was 3527 CP at 50°C.
[0090] Example 4
[0091] (1) 100.0 g of octamethylcyclotetrasiloxane, 6.0 g of methyltriethoxysilane, and 1.2 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred to obtain a silicone monomer mixture; 1.6 g of sodium hydroxide and 260.0 g of deionized water were added to a beaker, and the mixture was stirred to obtain a base catalyst solution.
[0092] (2) To a four-necked flask equipped with a constant temperature water bath jacket and a reflux condenser and a mechanical stirrer, 2.5 g of sodium dodecylbenzenesulfonate, 0.2 g of n-butanol, and 180 g of deionized water were added, and the mixture was stirred and heated to 50° C., and 10% of the organic silicon monomer mixture and 10% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The mixture was heated to 75° C. and reacted for 60 minutes. The remaining organic silicon monomer mixture and the acid catalyst were added dropwise within 5 hours, and the mixture was reacted at a constant temperature for 2 hours. The pH was adjusted to 8 with an aqueous sulfuric acid solution, and the silicone rubber core emulsion was obtained by filtration. The solid content was 41.4%, the average particle size was 246.11 nm, and the PDI was 0.092.
[0093] (3) 0.25 g of sodium dodecylbenzene sulfonate, 12.5 g of deionized water, 40.0 g of styrene, and 10.0 g of divinylbenzene were added to a beaker in sequence and emulsified using a high shear emulsifier for 8 min to obtain a styrene pre-emulsion;
[0094] 0.4 g of sodium dodecylbenzenesulfonate, 2.0 g of deionized water, 2.0 g of allyl glycidyl ether, 1.6 g of styrene, and 0.4 g of divinylbenzene were added to a beaker in sequence, and emulsified using a high shear emulsifier for 8 min to obtain an allyl glycidyl ether emulsion;
[0095] Add 1.0 g of sodium bicarbonate and 10.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0096] Add 0.54 g of potassium persulfate and 90.0 g of deionized water into a beaker, and stir to mix thoroughly to obtain a catalytic solution.
[0097] (4) To a four-necked flask equipped with a reflux condenser and a mechanical stirrer, 1.0 g of sodium dodecylbenzenesulfonate, 16.0 g of deionized water, 232.7 g of the silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C. Within 5 minutes, 50% of the styrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise, and the mixture was heated to 85° C. and reacted for 1.5 hours. The remaining styrene pre-emulsion and 30% of the catalyst solution were then added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 1.5 hours.
[0098] (5) Cooling to 70° C., adding the allyl glycidyl ether emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 min, heating to 85° C. and reacting for 1 h to prepare a silicone rubber core-shell emulsion with a solid content of 38.5%, an average particle size of 249.61 nm, and a PDI of 0.088.
[0099] (6) At room temperature, 480.0 g of cyclohexanone was added to the reactor, stirring was started, and 300.0 g of the silicone rubber core-shell emulsion was added dropwise within 2 min. Stirring was continued for 5 min after the addition was completed. Finally, the mixture was allowed to stand for 4 h until the upper and lower layers were completely separated. The lower layer was removed to obtain the upper transparent white silicone rubber core-shell dispersion with a solid content of 29.5%.
[0100] (7) 84.8 g of silicone rubber core-shell dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C and distilled under reduced pressure for 1 h without solvent removal to obtain a small-size active silicone rubber core-shell particle pre-dispersion (Z-4). The core-shell content was 25%, the average particle size was 252.10 nm, the PDI was 0.093, and the viscosity was 2506 CP at 50°C.
[0101] Example 5
[0102] (1) 100.0 g of octamethylcyclotetrasiloxane, 3.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 1.2 g of sulfuric acid and 90.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0103] (2) To a four-necked flask equipped with a constant temperature water bath jacket and a reflux condenser and a mechanical stirrer, 2.5 g of sodium dodecylbenzenesulfonate, 0.25 g of n-butanol, and 130.0 g of deionized water were added, and the mixture was stirred and heated to 50° C., and 60% of the organosilicon monomer mixture and 90% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The mixture was heated to 75° C. and reacted for 60 minutes. The remaining organosilicon monomer mixture and the acid catalyst were added dropwise within 1 hour, and the mixture was reacted at a constant temperature for 2 hours. The pH was adjusted to 8 with sodium hydroxide aqueous solution, and the silicone rubber core emulsion was filtered to obtain a solid content of 42%, an average particle size of 80.73 nm, and a PDI of 0.044.
[0104] (3) 0.25 g of sodium lauryl sulfate, 12.5 g of deionized water, 18.0 g of styrene, 2.0 g of butyl acrylate, and 5.0 g of divinylbenzene were added to a beaker in sequence and emulsified for 2 min using a high shear emulsifier to obtain a styrene pre-emulsion;
[0105] 0.2 g of sodium dodecylbenzenesulfonate, 1.0 g of deionized water, 1.0 g of allylamine, 0.8 g of styrene, and 0.2 g of divinylbenzene were added to a beaker in sequence, and emulsified for 2 min using a high shear emulsifier to obtain an allylamine emulsion;
[0106] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0107] Add 0.27 g of ammonium persulfate and 45.0 g of deionized water into a beaker, and stir to mix thoroughly to obtain a catalytic solution.
[0108] (4) To a four-necked flask equipped with a constant temperature water bath jacket and a reflux condenser and a mechanical stirrer, 0.5 g of sodium dodecylbenzenesulfonate, 7.3 g of deionized water, 232.7 g of silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C., 50% of the styrene pre-emulsion and 50% of the catalyst solution prepared in step (3) were added dropwise within 5 minutes, and the mixture was heated to 85° C. and reacted for 1 hour. The remaining styrene pre-emulsion and 30% of the catalyst solution were then added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 2 hours.
[0109] (5) Cooling to 70° C., adding the allylamine emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 min, heating to 85° C. and reacting for 1 h to prepare a silicone rubber core-shell emulsion with a solid content of 38.0%, an average particle size of 93.00 nm, and a PDI of 0.066.
[0110] (6) At room temperature, 200.0 g of ethyl acetate and 100.0 g of methyl acetate were added to the reactor, stirring was started, and 300.0 g of the silicone rubber core-shell emulsion was added dropwise within 2 min. Stirring was continued for 5 min after the addition was completed. Finally, the mixture was allowed to stand for 2 h. The upper and lower layers were completely separated. The lower layer was removed to obtain the upper transparent white silicone rubber core-shell dispersion with a solid content of 29.3%.
[0111] (7) 85.3 g of silicone rubber core-shell dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reactor and stirred evenly. The mixture was heated to 90°C and distilled under reduced pressure for 1 h without solvent distillation to obtain a small-particle active silicone rubber core-shell particle epoxy resin pre-dispersion (Z-5) with a core-shell content of 25%, an average particle size of 96.04 nm, a PDI of 0.009, and a viscosity of 2983 CP at 50°C.
[0112] Example 6
[0113] (1) 100.0 g of octamethylcyclotetrasiloxane, 3.0 g of methyltriethoxysilane, and 0.6 g of vinyltriethoxysilane were added to a beaker in sequence, and the mixture was stirred evenly to obtain a silicone monomer mixture; 1.2 g of sulfuric acid and 90.0 g of deionized water were added to a beaker, and the mixture was stirred evenly to obtain an acid catalyst solution.
[0114] (2) To a four-necked flask equipped with a constant temperature water bath jacket and a reflux condenser and a mechanical stirrer, 2.5 g of sodium dodecylbenzenesulfonate, 0.25 g of n-butanol, and 130.0 g of deionized water were added, and the mixture was stirred and heated to 50° C., and 60% of the organosilicon monomer mixture and 90% of the acid catalyst prepared in step (1) were added dropwise within 5 minutes. The mixture was heated to 75° C. and reacted for 60 minutes. The remaining organosilicon monomer mixture and the acid catalyst were added dropwise within 1 hour, and the mixture was reacted at a constant temperature for 2 hours. The pH was adjusted to 8 with sodium hydroxide aqueous solution, and the silicone rubber core emulsion was filtered to obtain a solid content of 42%, an average particle size of 80.73 nm, and a PDI of 0.044.
[0115] (3) 0.25 g of isotridecyl alcohol ether 1305, 12.5 g of deionized water, 20.0 g of styrene, 3.0 g of allyl glycidyl ether, and 5.0 g of divinylbenzene were added to a beaker in sequence, and the mixture was emulsified in a high shear emulsifier for 5 min to obtain a styrene pre-emulsion.
[0116] 0.2 g of sodium dodecylbenzenesulfonate, 1.0 g of deionized water, 1.0 g of allyl glycidyl ether, 0.8 g of styrene, and 0.2 g of divinylbenzene were added to a beaker in sequence, and emulsified using a high shear emulsifier for 5 min to obtain an allyl glycidyl ether emulsion;
[0117] Add 0.5 g of sodium bicarbonate and 5.0 g of deionized water to a beaker and stir to mix well to obtain a buffer solution;
[0118] Add 0.3 g of potassium persulfate and 45 g of deionized water into a beaker, and stir to mix evenly to obtain a catalytic solution.
[0119] (4) To a four-necked flask equipped with a constant temperature water bath jacket and a reflux condenser and a mechanical stirrer, 0.5 g of isomeric tridecanol ether 1305, 7.3 g of deionized water, 232.7 g of silicone rubber core emulsion, and the buffer solution prepared in step (3) were added, and the mixture was stirred and heated to 75° C., 30% styrene pre-emulsion and 40% catalytic solution prepared in step (3) were added dropwise within 5 minutes, and the mixture was heated to 85° C. and reacted for 1 hour. The remaining styrene pre-emulsion and 30% catalytic solution were then added dropwise within 30 minutes, and the mixture was reacted at a constant temperature for 2 hours.
[0120] (5) Cooling to 70° C., adding the allyl glycidyl ether emulsion prepared in step (3) and the remaining catalyst solution dropwise within 30 min, heating to 85° C. and reacting for 1 h to prepare a silicone rubber core-shell emulsion with a solid content of 37.9%, an average particle size of 95.10 nm, and a PDI of 0.077.
[0121] (6) At room temperature, 180.0 g of methyl isobutyl ketone, 10.0 g of ether, and 90.0 g of butanone were added to the reactor. Stirring was started and 300.0 g of silicone rubber core-shell emulsion was added dropwise within 2 min. Stirring was continued for 5 min after the addition was completed. Finally, the mixture was allowed to stand for 2 h. The upper and lower layers were completely separated. The lower layer was removed to obtain the upper transparent white silicone rubber core-shell dispersion with a solid content of 30.1%.
[0122] (7) 83.1 g of silicone rubber core-shell dispersion and 75.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to a reaction kettle and stirred evenly. The mixture was heated to 90°C and distilled under reduced pressure for 1 h without solvent removal to obtain a small-particle active silicone rubber core-shell particle epoxy resin pre-dispersion (Z-6). The core-shell content was 25%, the average particle size was 97.94 nm, the PDI was 0.049, and the viscosity was 2977 CP at 50°C.
[0123] 132.9 g of silicone rubber core-shell dispersion and 60.0 g of bisphenol A epoxy resin (Nan Ya 128) were added to the reactor and stirred evenly. The mixture was heated to 90°C with stirring and distilled under reduced pressure for 1.5 h without solvent distillation to obtain silicone rubber core-shell particle epoxy resin pre-dispersion (Z-6-1). The core-shell content was 40%, the average particle size was 98.03 nm, the PDI was 0.030, and the viscosity was 20013CP at 50°C.
[0124] 132.9 g of silicone rubber core-shell dispersion and 60.0 g of alicyclic epoxy resin (Dacel 2021P) were added to the reactor and stirred evenly. The mixture was heated to 90°C with stirring and distilled under reduced pressure for 1.5 h without solvent distillation to obtain a rubber core-shell particle alicyclic epoxy resin pre-dispersion (Z-6-2) with a core-shell content of 40%, an average particle size of 98.10 nm, a PDI of 0.091, and a viscosity of 12329 CP at 50°C.
[0125] The parameters of Examples 1-6 are summarized in Table 1.
[0126] Table 1
[0127]
[0128]
[0129] Example 7
[0130] To the epoxy resin pre-dispersion liquid (Z-1) 144.0 g (core-shell ratio 25%) obtained in Example 1, 8.0 g of neodecanoic acid glycidyl ester E-10P (Hansen HEXION E10P) as a reactive diluent, 8.0 g of dicyandiamide (Aladdin reagent, ≥99%) as a curing agent, 1.0 g of aromatic dimethyl urea (Azken accelerator DYHARD UR300) as a curing accelerator, 2 g of silica (Cabot white carbon black CAB-O-SIL TS720), 0.3 g of carbon black (Cabot MONARCH120 carbon black), 10.0 g of nano-calcium carbonate (Zhengzhou Yufeng Nanomaterial Co., Ltd.), and 5.0 g of calcium oxide (Aladdin reagent, reagent grade) were added. After mixing with a vacuum degassing mixer, the mixture was mixed and stirred 3 times with a three-roll mill to obtain an adhesive composition (S-1) containing core-shell particles.
[0131] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-1) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with GB / T36877-2018. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for 1 hour.
[0132] Example 8
[0133] The epoxy resin pre-dispersion liquid (Z-1) was replaced by the epoxy resin pre-dispersion liquid (Z-2), and the remaining steps were the same as those in Example 7, and an adhesive composition (S-2) containing core-shell particles was obtained.
[0134] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-2) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with GB / T36877-2018. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for 1 hour.
[0135] Example 9
[0136] The epoxy resin pre-dispersion liquid (Z-1) was replaced by the epoxy resin pre-dispersion liquid (Z-3), and the remaining steps were the same as those in Example 7, to obtain an adhesive composition (S-3) containing core-shell particles.
[0137] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-3) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with the GB / T36877-2018 standard. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for 1 hour.
[0138] Example 10
[0139] The epoxy resin pre-dispersion liquid (Z-1) was replaced by the epoxy resin pre-dispersion liquid (Z-4), and the remaining steps were the same as those in Example 7, and an adhesive composition containing core-shell particles (S-4) was obtained.
[0140] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-4) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with the GB / T36877-2018 standard. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for 1 hour.
[0141] Example 11
[0142] The epoxy resin pre-dispersion liquid (Z-1) was replaced by the epoxy resin pre-dispersion liquid (Z-5), and the remaining steps were the same as those in Example 7, to obtain an adhesive composition (S-5) containing core-shell particles.
[0143] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-5) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with GB / T36877-2018. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for one hour.
[0144] Comparative Example 1
[0145] To 90.0 g of KANE ACE MX-154 (bisphenol A epoxy resin: 60%, butadiene core-shell rubber particles: 40%, average particle size: 100 nm) was added bisphenol A epoxy resin (Nan Ya 128) to obtain an epoxy resin composition (Z-7, core-shell ratio 25%).
[0146] The epoxy resin pre-dispersion liquid (Z-1) was replaced with the epoxy resin composition (Z-7), and the remaining steps were the same as those in Example 7, to obtain an adhesive composition (S-7) containing core-shell particles.
[0147] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-7) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with GB / T36877-2018. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for one hour.
[0148] Comparative Example 2
[0149] Product Name: KANE ACE MX-960 (bisphenol A epoxy resin: 60%, silicon core-shell rubber particles: 40%, average particle size: 300nm) Epoxy resin composition (Z-8, core-shell ratio 25%)
[0150] The epoxy resin pre-dispersion liquid (Z-1) was replaced with the epoxy resin composition (Z-8), and the remaining steps were the same as those in Example 7, to obtain an adhesive composition (S-8) containing core-shell particles.
[0151] Symmetrical wedge impact test specimens were prepared using the resulting core-shell particle-containing adhesive composition (S-8) and two aluminum alloy plates (6061 aluminum) with a thickness of 0.8 mm, a width of 20 mm, and a length of 90 mm, in accordance with the GB / T36877-2018 standard. The bond thickness was adjusted to 0.25 mm, and the core-shell particle-containing adhesive composition was cured by heating at 170°C for one hour.
[0152] The evaluation results of various physical properties of Examples 1-5 and Comparative Examples 1-2 are summarized in Table 2
[0153] Table 2
[0154]
[0155] 1. Silicone rubber particle size core: Examples 7-11, Comparative Example 2
[0156] As shown in Table 2, by comparing Examples 7-11 and Comparative Example 2, it can be seen that as the particle size decreases, the impact resistance and adhesion are significantly improved regardless of room temperature or low temperature. Within the existing particle size range, the smaller the particle size, the better the toughening effect, which is higher than the commercially available one. It should be noted that the outer layer of Example 11 is an amino group, and the others are epoxy groups. In comparison, these two functional groups have a smaller direct impact.
[0157] 2. Comparison of silicone rubber core and butadiene core: Examples 7-11, Comparative Examples 1-2
[0158] As shown in Table 2, by comparing Examples 7-11 and Comparative Example 1, it can be seen that the particle sizes of the silicone rubber core of 97.63 nm (Example 1) and the polybutadiene core of 100 nm (Comparative Example 1) are basically around 100 nm, but the impact resistance and adhesion of the silicone rubber core are significantly higher than that of the butadiene core.
Claims
1. A method for preparing an epoxy resin pre-dispersion liquid, characterized in that: Here are the steps: (1) By weight, 500 parts of an organosilicon monomer, 1-100 parts of a silane coupling agent, and 1-100 parts of a double-bond silane coupling agent are uniformly mixed to obtain an organosilicon monomer mixed solution; 1-50 parts of an acid or base catalyst and 1-500 parts of water are uniformly mixed to obtain an acid or base catalyst solution; (2) By weight, 1-50 parts of emulsifier, 0-50 parts of co-emulsifier, 0-400 parts of water and 0%-100% of the acid or base catalyst prepared in step (1) are mechanically stirred and heated to 20°C-90°C, 1%-100% of the organosilicon monomer mixture prepared in step (1) and 0%-100% of the acid or base catalyst are dropwise added within 1 min-360 min, the temperature is raised to 50°C-95°C and the reaction is carried out for 5 min-240 min, the remaining organosilicon monomer mixture and acid or base catalyst are dropwise added within 0.5 h-6 h, the reaction is carried out at a constant temperature for 1 h-6 h, the temperature is lowered to 10-40°C, the pH is adjusted to 4-10, and the silicone rubber core emulsion is obtained by filtration; (3) By weight, 1-50 parts of double bond-containing monomer, 0.01-5 parts of emulsifier, and 3-30 parts of water are emulsified in a high shear emulsifier for 1 minute to 10 minutes to obtain a double bond-containing pre-emulsion; 1-25 parts of functional monomer, 1-50 parts of double bond-containing monomer, 0.01-5 parts of emulsifier, and 1-50 parts of water are emulsified in a high shear emulsifier for 1 min-10 min to obtain a functional monomer emulsion; 0-1 parts of buffer and 0-50 parts of water are stirred and dissolved to obtain a buffer solution; 0.01-5 parts of catalyst and 1-500 parts of water are stirred and dissolved to obtain a catalyst solution; (4) By weight, 100 parts of silicone rubber core emulsion, 0.01-5 parts of emulsifier, 1-50 parts of water and the buffer solution prepared in step (3) are stirred and heated to 40-90°C, 1%-60% of the double bond-containing pre-emulsion prepared in step (3) and 1%-100% of the catalyst solution are added dropwise within 1 min-30 min, the temperature is raised to 50-90°C, and the reaction is carried out for 1 min-120 min. After the remaining double bond-containing pre-emulsion and 1%-99% of the catalyst solution are added dropwise within 0.5 h-4 h, the temperature is raised to 60-95°C and the reaction is carried out for 0.5 h-6 h; (5) Cooling to 30-90°C, adding the functional monomer emulsion prepared in step (3) and the remaining catalyst solution dropwise within 1 min-120 min, heating to 50-95°C and reacting for 0.5 h-6 h to prepare a silicone rubber core-shell emulsion; (6) Add 20-400 parts of solvent by weight to the reaction kettle, start stirring at room temperature, and add 100 parts of silicone rubber core-shell emulsion dropwise within 1 minute to 60 minutes for extraction. Continue stirring for 1 minute to 30 minutes after the addition, and then let it stand for 0.5 hours to 24 hours to separate the layers. Remove the lower water layer to obtain the upper silicone rubber core-shell particle solvent dispersion; (7) 10-1000 parts by weight of the prepared silicone rubber core-shell particle solvent dispersion and 100 parts by weight of epoxy resin are added to a reaction kettle and stirred, and then the temperature is raised to 60-120°C, and the solvent is removed by vacuum distillation for 0.5h-24h to prepare an epoxy resin pre-dispersion.
2. The method for preparing an epoxy resin pre-dispersion liquid according to claim 1, wherein The organosilicon monomer in step (1) is one of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, octaphenylcyclotetrasiloxane, methylphenylcyclosiloxane, tetravinyltetramethylcyclotetrasiloxane, and low molecular weight hydroxy silicone oil, or a combination thereof; The silane coupling agent in step (1) is one of methyltrimethoxysilane, methyltriethoxysilane, octyltriethoxysilane, phenyltrimethoxysilane, phenyltrimethoxysilane, tetraethyl silicate, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-mercaptopropyl-trimethoxysilane, or a combination thereof; The double bond-containing silane coupling agent in step (1) is one of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, and vinyl-tris(2-methoxyethoxy)silane, or a combination thereof; The acid catalyst in step (1) is one or a combination of benzenesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, formic acid, perchloric acid, etc.; the base catalyst is one or a combination of sodium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, ammonia water, sodium oxide, potassium oxide, sodium methoxide, sodium ethoxide, potassium ethoxide, sodium tert-butoxide, tetramethylammonium hydroxide.
3. The method for preparing an epoxy resin pre-dispersion according to claim 1, wherein: The emulsifier in steps (2) to (4) is one of sodium lauryl sulfate, sodium cetyl sulfate, sodium docusate, sodium dodecyl sulfonate, sodium dodecylbenzenesulfonate, dodecylbenzenesulfonic acid, sodium didodecylphenyl ether disulfonate, fatty acid polyoxyethylene phosphate, sodium rosinate, sodium cyclohexane, sodium ricinoleate, isomeric tridecyl alcohol ether, polyoxyethylene octylphenol ether-10, sorbitan monolaurate, sorbitan monopalmitate, dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, and dodecyldimethylbenzylammonium chloride, or a combination thereof; The co-emulsifier in step (2) is one of n-butanol, n-pentanol, ethylene glycol, ethanol, propylene glycol, isopropyl alcohol, polyvinyl alcohol, polyethylene glycol, acetone, butanone, ethyl acetate, methyl acetate, glycerol, polyglycerol ester, sodium chloride, sodium sulfate, sodium bicarbonate, or a combination thereof.
4. The method for preparing an epoxy resin pre-dispersion according to claim 1, wherein: In step (2), the pH is adjusted using an alkaline aqueous solution or an acidic aqueous solution, wherein the alkaline aqueous solution is one of ammonia water, sodium hydroxide aqueous solution, sodium bicarbonate aqueous solution, sodium formate aqueous solution, sodium acetate aqueous solution, ammonium acetate aqueous solution, disodium hydrogen phosphate aqueous solution, dipotassium hydrogen phosphate aqueous solution, sodium pyrophosphate aqueous solution, and sodium phosphate aqueous solution, or a combination thereof; the acidic aqueous solution is one of benzenesulfonic acid aqueous solution, p-toluenesulfonic acid aqueous solution, dodecylbenzenesulfonic acid aqueous solution, hydrochloric acid aqueous solution, sulfuric acid aqueous solution, phosphoric acid aqueous solution, acetic acid aqueous solution, formic acid aqueous solution, and perchloric acid aqueous solution, or a combination thereof.
5. The method for preparing an epoxy resin pre-dispersion according to claim 1, wherein: The double bond-containing monomer in step (3) is one of styrene, acrylonitrile, methyl methacrylate, butyl acrylate, isooctyl acrylate, acrylic acid, lauryl methacrylate, acrylamide, glycidyl methacrylate, allyl glycidyl ether, allylamine, 4-vinylaniline, 4-penten-1-amine, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 1-penten-3-ol, acrylic acid, methacrylic acid, methylenediamine, maleic acid, crotonic acid, allyl methacrylate, divinylbenzene, dicyclopentadiene acrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, trimethylolpropane trimethacrylate, triallyl isocyanurate, and ethoxypentaerythritol tetraacrylate, or a combination thereof.
6. The method for preparing an epoxy resin pre-dispersion liquid according to claim 1, wherein: The functional monomer is one of epoxy-containing functional monomers, amino-containing functional monomers, hydroxyl-containing functional monomers, and carboxyl-containing functional monomers, or a combination thereof.
7. The method for preparing an epoxy resin pre-dispersion liquid according to claim 6, characterized in that: The epoxy-containing functional monomer is one of glycidyl methacrylate and allyl glycidyl ether or a combination thereof; the amino-containing functional monomer is one of allylamine, 4-vinylaniline, and 4-pentene-1-amine or a combination thereof; the hydroxyl-containing functional monomer is one of hydroxyethyl methacrylate, hydroxypropyl methacrylate, and 1-pentene-3-ol or a combination thereof; and the carboxyl-containing functional monomer is one of acrylic acid, methacrylic acid, methylene succinic acid, maleic acid, and crotonic acid or a combination thereof.
8. The method for preparing an epoxy resin pre-dispersion according to claim 1, wherein: The buffering agent in step (3) is one of sodium bicarbonate, sodium formate, sodium acetate, ammonium acetate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, sodium pyrophosphate, sodium phosphate, or a combination thereof; The catalyst in step (3) is one of diisopropylbenzene peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, benzoyl peroxide, azobisisobutylonitrile initiator, azobisisoheptylonitrile, or a combination thereof.
9. The method for preparing an epoxy resin pre-dispersion according to claim 1, wherein: The solvent described in step (6) is one of methyl formate, ethyl acetate, vinyl acetate, cyclohexanone, acetone, butanone, methyl isobutyl ketone, ethanol, isopropanol, triethylene glycol, propylene glycol, diethanolamine, triethanolamine, cyclohexane, n-hexane, n-heptane, xylene, toluene, dimethylformamide, acetonitrile, N-methylpyrrolidone, ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol butyl ether, styrene, perchloroethylene, trichloroethylene, ethylene glycol ether, chloroform, dichloroethane, and dichloromethane, or a combination thereof.
10. The method for preparing an epoxy resin pre-dispersion liquid according to claim 1, characterized in that: The epoxy resin described in step (7) is one of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, epoxidized olefin compound, heterocyclic and mixed epoxy resins, or a combination thereof.
Citation Information
Patent Citations
Preparation method of nano silicone rubber core-shell structure polymer toughened epoxy resin
CN114685943A
Toughening and enhancing type nano core-shell particle toughening agent as well as preparation method and application thereof
CN118271792A
Composition of acryl-silicone complex, preparing method and use thereof
US20070100073A1